CONTRASTING DUALITY AND ITS SIGNIFICANCE IN ANDALUSIAN POETRY, THE ERA OF THE SOVEREIGNTY OF CORDOBA AS A MODEL - Ammar Abbas Hamid Khalaf Al-Mohammadi; Bashar Khalaf Abboud Saeed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The duality in which the world of color is used is closer to the world of painting than to the world of poetry because it expresses its being directly, which has effectiveness by addressing the conscience directly by placing it within a linguistic context, which has a meaning in the construction of the poetic sentence and then the poem. Hence, we find that the poet Andalusian innovated through his use of the duality of color to reach the feelings of the recipient and influence his conscience by using color through poetic paintings that accommodate the extent of suffering in his private and public issues color contrast.